Course on Educational Web-Content Accessibility: Analysis of Online Learning Results - Ye. A. Kosova (Открытое образование (Москва))
Purpose of research. The paper deals with the analysis of the learning outcomes of non-degree students in the first online course in the Russian Federation on the development of accessible educational webcontent. Analysis of the problems of online education shows that open online courses are inaccessible for people with disabilities, education online platforms do not comply with the principles of accessibility, lecturers do not have experience in teaching methods of using distance learning technologies in e-learning for the people with disabilities, web developers have little knowledge of web accessibility guidelines and policies. Thus, the development of curricula and courses on the basics of web accessibility and universal design for e-learning stakeholders belongs to current didactic tasks.Materials and methods. The study analyzed the learning outcomes in a free course “Web accessibility in e-learning” (Stepik platform) in the period from 10 February to 11 November 2020 (491 participants). Statistical data of Stepik used for analysis and included: date of enrollment in the course; the results of tasks’ passing and the content of the students’ answers; the results of each student’s progress in steps, modules and final testing; the number of views, correct and incorrect decisions for each step; indexes of complexity and discriminatory power (distinctiveness) of tasks for each step. Data processing (sorting, filtering and grouping by attributes, calculating weighing coefficients and mean values) and graphical presentation of the results are performed in Microsoft Excel®. The analysis of the starting survey results was carried out in the program IBM SPSS Statistics 23 by methods of descriptive statistics (construction of frequency tables and cross tables).Results. Analysis of the course enrollment showed weak user activity. 212 (43.2%) enrolled students successfully completed the course. Most of the students missed the optional types of work. At the same time, on average, users have successfully completed the current and final testing. Difficulty value indexes (0.51 ± 0.18) and discriminatory power indexes (0.35 ± 0.17) of the tests indicate that the test tasks have a moderate level of complexity. A comparative analysis of the discriminative indexes for different types of tests showed that case-tests have a greater discriminative power (0.41 ± 0.15) than classical tests (0.26 ± 0.09) with similar difficulty value indexes. According to self-assessment data, students made significant progress in the formation of accessible educational web-content (by 55.2%), which is consistent with the data of an objective assessment of knowledge, skills and abilities during the final testing.Conclusion. An analysis of the activity and learning outcomes in the course “Web accessibility in e-learning” showed that target category of students do not always realize the need for development of professional competencies to create accessible educational web-content. The biggest problems are associated with attracting the audience to the course and insufficient self-discipline due to the lack of motivation of students. Under these circumstances, an optional approach to learning the basics of web accessibility is not enough. Technologies for the development of accessible educational web-content should be taught as a compulsory subject at all stages of lifelong education for specialists involved in the organization of e-learning